Social classes, consumption and symbolic violence - Campos, Rebeca Rebollo de (Faculdade de Ciências e Letras - Unesp - Araraquara., 2015)
This article deals with the concept of symbolic violence of Pierre Bourdieu in the context of social and economic changes Brazilian. Symbolic violence at school has the main institution of social reproduction, but it can be perceived in other instances, such as family, religion; and in this article, will be worked mainly in its economic context, through consumption. With the real minimum wage increase above inflation during the Lula government, increasing the number of formal jobs and extension of credit, a larger portion of the population now has access to goods and services before they were restricted. The consumer electronics, cars, housing, designer clothes and trips caused discomfort in the upper classes, affecting how conflicts and disputes by physical spaces as well as disputes in the symbolic field occur. The contempt and the struggle of the upper classes to distinguish the new consumer assumes forms and increasingly declared strategies. The internet and social networks are important tools in this article because it is through them that will be evaluated cases of symbolic violence between classes will be selected cases of violence and intolerance through consumption and access goods and services.